Challenges of rabies surveillance in Madagascar based on a mixed method survey amongst veterinary health officers - Dreyfus, Anou; Volasoa, Marie Hermelienne; Guis, Hélène; Razafindraibe, Nivohanitra Perle; Razafindramparany, Mino Harimbola; Arivony, Nomenjanahary Lalaina; Rakotondrabe, Naltiana; Andriamananjara, Mamitiana Aimé; Dussart, Philippe; Kassie, Daouda; Lacoste, Vincent; Andriamandimby, Soa Fy (Frontiers in Veterinary Science, 2024)
In Madagascar, rabies is endemic and a notifiable disease. The objective of this mixed study was to understand the challenges faced by the Veterinary Health Officers (VHOs) in the current rabies surveillance system in Madagascar. A survey was conducted from mid-April to the end of July 2021 during which all officially-listed VHOs (N=150) were contacted by phone at least twice. Participants (n=90), representative of the 22 regions of Madagascar, were interviewed by phone based on a semi-structured questionnaire on (1) their knowledge of rabies epidemiology in their area of activities, (2) the occurrence of human and animal rabies and the species affected in the region where they work, (3) the factors that might influence rabies surveillance depending on (a) their activities and area of operation, (b) the socio-cultural aspects of local communities, and (c) the general organization of animal rabies surveillance. The majority (80/90) of VHOs representing all 22 regions declared having been informed of at least one suspected or confirmed case of human and/or animal rabies in their area of activity during their work as VHOs: at least once a month for 11 of them, at least once a year for 40 and with undetermined frequency for 29. Several obstacles hinder the surveillance of rabies resulting in under-reporting. The lack of funds to access suspect animals, collect, pack and ship samples in compliance with biosecurity measures and the cold chain, was mentioned as a major obstacle to surveillance. The second barrier is socio-cultural: in many large coastal regions, dogs are taboo and VHOs fear rejection by the community if they treat dogs. While the general population requires information on the rabies situation in Madagascar and on how to proceed in the event of a bite, veterinarians and decision-makers need to be fully aware of an evidence-based approach to rabies surveillance, prevention and control. Communication between the human and animal health sectors should be improved. Politicians need to be persuaded of the importance of funding to eliminate rabies in Madagascar. The adoption, in early 2023, of a national strategic plan for rabies control is a first step in this direction.